2009
DOI: 10.1002/14651858.cd000996.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled steroids for bronchiectasis

Abstract: Edwards 2003 Edwards EA, Asher MI, Byrnes CA. Paediatric bronchiectasis in the twenty-first century: experience of a tertiary children's hospital in New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 31 publications
0
53
0
4
Order By: Relevance
“…As pointed out in a recent Cochrane review, the absence of high-quality evidence means that decisions to use or discontinue combined ICS and long-acting β-adrenoceptor agonist (LABA) in people with bronchiectasis may need to take account of the presence or absence of co-existing airway hyper-responsiveness and consideration of potential adverse events associated with combined ICS-LABA [71,72]. These adverse effects include the recently noted increase in pneumonia risk in COPD patients [73].…”
Section: Inhaled Corticosteroids and Bronchodilatorsmentioning
confidence: 99%
“…As pointed out in a recent Cochrane review, the absence of high-quality evidence means that decisions to use or discontinue combined ICS and long-acting β-adrenoceptor agonist (LABA) in people with bronchiectasis may need to take account of the presence or absence of co-existing airway hyper-responsiveness and consideration of potential adverse events associated with combined ICS-LABA [71,72]. These adverse effects include the recently noted increase in pneumonia risk in COPD patients [73].…”
Section: Inhaled Corticosteroids and Bronchodilatorsmentioning
confidence: 99%
“…A 2009 review showed insufficient evidence to recommend the routine use of inhaled corticosteroids in adults with stable bronchiectasis 47. Our analysis only included 163 eligible patients for the efficacy of inhaled corticosteroids, showing no effect on exacerbations, hospitalisation or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by He et al have suggested that cumulative doses of corticosteroids exceeding 350 mg are highly related to IPA occurrence in COPD patients (14,15), and some reports have even evoked a plausible role for inhaled steroids in its emergence (16)(17)(18). It has also been shown that immune dysfunction and bacterial persistence in NCFB are associated with the use of antiinflammatory agents, such as inhaled corticosteroids (19), and long-term antibiotic treatment (20,21).…”
Section: Discussionmentioning
confidence: 99%